Recurrent embolisms despite adequate anticoagulant therapy in a patient with prosthetic heart valves and atrial fibrillation: a case report. Issue 7 (24th July 2021) - Marschall, Alexander; Rodriguez Torres, Diego; Rueda Liñares, Andrea; Martí Sánchez, David
Abstract: Background: Antithrombotic management in patients with atrial fibrillation (AF) that have undergone heart valve surgery may be challenging, especially in the context of thromboembolic events during follow-up. The combination of pharmacological therapies with modern transcatheter interventions allows these more complex cases to be overcome. Case summary: We present the case of a 66-year-old female with a history of AF and mechanical aortic and mitral valve replacement, which was admitted to the hospital complaining of dizziness and unsteady gait. A computerized tomography scan of the brain confirmed the diagnosis of embolic stroke. Two years later, the patient complained of sudden onset of chest pain, accompanied by electrocardiographic abnormalities and elevated high-sensitivity troponin T. Emergency cardiac catheterization revealed embolic myocardial infarction with distal occlusion of the obtuse marginal artery. Again, 2 years later, the patient suffered a new cerebral embolic event. Given the adequate anticoagulation therapy throughout almost the entire clinical course, percutaneous left atrial appendage closure was proposed as an adjunct to vitamin K antagonist treatment. Notably, intraprocedural transoesophageal echocardiography revealed the presence of a previously undetected left atrial appendage thrombus, thus an embolic protection device was used during the procedure, which was successfully carried out without complications. Discussion: This case report demonstrates the complexity of the antithrombotic management in patients with AF and prosthetic heart valves, and highlights the importance of an individualized approach, integrating new therapeutic strategies to achieve success, in patients that present thromboembolic events despite adequate anticoagulation therapy.